Diagnostic biomarker KIF23 is associated with immune infiltration and immunotherapy response in gastric cancer - Bai, Maoshu; Liu, Xin (Frontiers in Oncology, 2023)
Kinesin family member 23 (KIF23), an index of tumor proliferation, can serve as a prognostic marker in numerous tumors. However, the relationship between KIF23 expression and diagnostic value, immune infiltration, and immunotherapy response remains unclear in gastric cancer(GC). We primarily demonstrated that GC tissue had higher levels of KIF23 expression than the adjacent normal tissue on mRNA and protein levels. The ROC analysis revealed KIF23 had an outstanding diagnostic value of GC in the training and validation set (AUC = 0.958, and AUC = 0.86793, respectively). We discovered that KIF23 was positively associated with age, histological type, and H. pylori infection of GC. Subsequently, the KIF23 expression level was correlated with the gene mutation, function enrichment, immune cell infiltration, and immune cell marker of GC based on multiple online websites and R software. KIF23 expression was related to the infiltration of CD8+ T cells, CD4+T cells, macrophages, and dendritic cells in GC. In addition, KIF23 expression was positively significantly associated with the Th1 cell marker STAT1 (Signal transducer and activator of transcription 1). Patients with high KIF23 expression exhibited a greater level of immune cell infiltrates, including T cell CD4+ memory helper, Treg, and M1 cells, which indicated that high KIF23 expression is more conducive to immunosuppression. Finally, KIF23 expression had a positive relationship with TMB and MSI, and affected the immune microenvironment in GC tissues by increased expression of ICPs such as CD274(PD-L1), CTLA4, HAVCR2, and LAG3. Our study uncovered that KIF23 can serve as an immune-related biomarker for diagnosis and immunotherapy response of GC.